EFFECT OF PIMPINELLA TIRUPATIENSIS TUBEROUS ROOT EXTRACT IN RESTORATION OF ALTERATIONS IN RENAL CARBOHYDRATE METABOLIC PROFILE IN STZ INDUCED DIABETIC RATS - T. LAVANYA,; REDDY, S. RAJESWARA; G. NARASIMHULU,; REDDY, K. SATHYAVELU (The Bioscan, 2010)
Pimpinella tirupatiensis (Pt) is an endemic plant of Seshachalam hills of India. In the present study, the effect of Pimpinella tirupatiensis in diabetic rats has been investigated. An optimum dose of Pt ethyl alcohol extract (750 mg/kg body weight) was orally administered for 30 days to streptozotocin (STZ) induced diabetic rats for the assessment of total carbohydrate (TCH), total proteins (TP), free amino acids (FAs), pyruvate and lactate, in normal and STZ-diabetic rat renal tissue. A significant (p<0.01) reduction in the levels of TCH, TP, and pyruvate were observed in the kidney of diabetic rats. FAs and lactate levels were enhanced in diabetic control rats. Pt at 750mg/kg b.w dose enhanced the levels of TCH, TP, and pyruvate significantly. FAs and lactate levels were decreased significantly with the treatment of Pt. Pt produced similar beneficial effects on all biochemical parameters studied as that of glibenclamide (Glb), a standard anti diabetic drug. These results indicate that Pt possesses anti diabetic activity and other pharmacological properties.